A metabolic history of manufacturing waste: food commodities and their outsides. (20th October 2019) - Landecker, Hannah
ABSTRACT: The early twentieth-century industrialization of food production and processing generated large volumes of processing waste. Following the fate of waste products cast off from the new food commodities, this article describes the logics and practices of large-scale waste reuse as animal feed and microbial nutrient medium in industrial chemical production in the United States. A "chemical gaze" on matter recast disparate burdensome byproducts such as beet pulp, cottonseed meal, or arsenic trioxide in terms of resources to be fed forward through microbial and animal metabolism. Focused on feed efficiency and growth promotion, this chemical gaze was selectively attuned to growth yet blind to the emerging infrastructure of waste-as-feed as a massive circulatory system for both nutrients and the toxicants introduced by growth promoters. Following metabolic pathways of materials over time, this history is at once an account of animal feed systems in twentieth-century America, and a tracing of the externalities of food commodities as they pass through different chemical forms.